Numerical simulation of a novel ocean wave energy converter. (August 2018) - Jafari, Mohammad; Babajani, Aliakbar; Hafezisefat, Parinaz; Mirhosseini, Mojtaba; Rezania, Alireza; Rosendahl, Lasse
Abstract: Ocean waves are one of the energy resources, which have a potential to supply some parts of the world's energy requirements. Recently, many researchers are interested in investigation of the ocean wave energy conversion (OWEC), because energy generation from this device is considered renewable and clean energy. A new wave energy converter named "Searaser" was invented with new technology in 2013. The primary aim of this research is to study the capability of Flow-3D commercial software in simulation of this energy converter. In order to validate the results, a comparison was made between numerical and experimental research, which showed a good agreement in motion of buoy. In this research, wave energy converter was simulated inside a wave tank including water. Furthermore, Reynolds Averaged Navier-Stokes equations were coupled with volume of fluid (VOF) model to generate three-dimensional numerical linear propagating waves as well as solving the fluid flow. Pressure and velocity contours were shown when wave passes the buoy. Although different methods are used for mesh generation of solid and fluid domains in this software, results indicate the capability of Flow-3D software for modelling the fluid structure interaction (FSI) problems including wave motions. However, more parametric studies need to be conducted for this new energy converter to illustrate more details about the power generation of this energy converter.